Early Marriage Age Trends in Magetan Regency, Indonesia: A Review of 2021-2023 - Rifky Ayu Kusumaningtias; Tinuk Esti Handayani; Suparji Suparji; Astin Nur Hanifah (Health Dynamics, 2024)
Background: Early marriage is a significant women's reproductive health issue, especially because of its association with the risk of abortion, stunting, malnutrition and infection in infants. The aim of the study was to describe the age trend of early marriage in Magetan Regency from 2021 to 2023. Methods: This type of research is descriptive quantitative with the population of all couples who married in Magetan Regency during the period. The sample of this study included all married individuals with a total of 12,772 people. The main variable was age at marriage. Data were collected through a documentation study of age of marriage reports recorded at the PPKBPP and PA Office of Magetan Regency using a data recapitulation table. Data analysis was conducted with descriptive statistics, in the form of frequency distribution and percentage. Results: The results showed an increasing trend of early marriage in most sub-districts, with a predicted prevalence that tends to increase until the end of 2024. Between 2021 and 2023, the trend of early marriage age in Magetan Regency showed a varied pattern, with some years increasing and others decreasing. The main factors influencing this trend include economic factors, education, and local policies. The impacts of early marriage include challenges in health and education, which require continued attention in mitigation and response efforts. Conclusion: The conclusion of this study is that there is a need for serious attention to this problem, including prevention efforts through education, counseling, and improving the quality of education and policies to prevent early marriage from the government and related institutions.